Impact of the in situ formed salivary pellicle on enamel and dentine erosion induced by different acids - Wiegand, Annette; Bliggenstorfer, Salome; Magalhaes, Ana Carolina [UNESP]; Sener, Beatrice; Attin, Thomas (Informa Healthcare, 2008)
Objective. To investigate and compare the protective impact of the in situ formed salivary pellicle on enamel and dentine erosion caused by different acids at pH 2.6. Methods. Bovine enamel and dentine samples were exposed for 120 min in the oral cavity of 10 healthy volunteers. Subsequently, enamel and dentine pellicle-covered specimens were extraorally immersed in 1 ml hydrochloric, citric or phosphoric acid (pH 2.6, 60 s, each acid n=30 samples). Pellicle-free samples (each acid n=10) served as controls. Calcium release into the acid was determined by atomic absorption spectroscopy. The data were analysed by two-way ANOVA and Tukey's test (alpha=0.05). Results. Pellicle-covered samples showed significantly less calcium loss compared to pellicle-free samples in all acid groups. The mean (SD) pellicle protection (% reduction of calcium loss) was significantly better for enamel samples [60.9 (5.3)] than for dentine samples [30.5 (5.0)], but revealed no differences among the acids. Conclusion. The efficacy of the in situ pellicle in reducing erosion was 2-fold better for enamel than for dentine. Protection of the pellicle was not influenced by the kind of acid when enamel and dentine erosion was performed at pH 2.6.
Keywords: acid; dentine; enamel; erosion; pellicle